Morphology of Javan Broadhead Planarian (Bipalium Javanum) - Ni’mah, Zumrotun; Luthfi, M. Jafar (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Indonesia is one of the countries at the center richest biodiversity in the world, so that Indonesia is referred to as megabiodiversity country. One of the typical fauna in Indonesia is the broadhead planarian Javan (Bipalium javanum). Javan Broadhead Planarian is a parasitic worm that lives in humid areas and is protected from sunlight. Little research has been done on the Javan Broadhead Planarian, especially in terms of morphology. This research was conducted to determine the morphology and characteristics of the planarian broadhead javan. The research was conducted in two stages. The first stage is taking samples of worms at Kedung Pedut Kulon Progo Waterfall. The second stage is taking morphological image data. Data collection of habitat, behavior, dorsal and ventral body parts was carried out using a macrolens camera, and headplate and creeping sole image data were taken using a stereo microscope. The data taken is in the form of image data taken using a camera with a macro lens and a stereo microscope. Based on the research conducted, the results obtained from the image data of the habitat, behavior, headplate, dorsal and ventral body parts, and creeping sole.